Genetic polymorphisms of PIP5K2A and course of schizophrenia - Evgeniya G. Poltavskaya; Olga Yu. Fedorenko; Natalya M. Vyalova; Elena G. Kornetova; Nikolay A. Bokhan; Anton J. M. Loonen; Svetlana A. Ivanova (BMC, 2020)
Abstract Background Schizophrenia is a severe highly heritable mental disorder. The clinical heterogeneity of schizophrenia is expressed in the difference in the leading symptoms and course of the disease. Identifying the genetic variants that affect clinical heterogeneity may ultimately reveal the genetic basis of the features of schizophrenia and suggest novel treatment targets. PIP5K2A (Phosphatidylinositol-4-Phosphate 5-Kinase Type II Alpha) has been investigated as a potential susceptibility gene for schizophrenia. Methods In this work, we studied the possible association between eleven polymorphic variants of PIP5K2A and the clinical features of schizophrenia in a population of 384 white Siberian patients with schizophrenia. Genotyping was carried out on QuantStudio 5 Real-Time PCR System with a TaqMan Validate SNP Genotyping Assay (Applied Biosystems, USA). Results PIP5K2A rs8341 (χ2 = 6.559, p = 0.038) and rs946961 (χ2 = 5.976, p = 0.049) showed significant association with course of schizophrenia (continuous or episodic). The rs8341*CT (OR = 1.63, 95% CI: 1.04-2.54) and rs946961*CC (OR = 5.17, 95% CI: 1.20-22.21) genotypes were associated with a continuous type of course, while the rs8341*TT genotype (OR = 0.53, 95% CI: 0.29-0.97) was associated with an episodic type of course of schizophrenia. Therefore rs8341*TT genotype presumably has protective effect against the more severe continuous course of schizophrenia compared to the episodic one. Conclusions Our experimental data confirm that PIP5K2A is a genetic factor influencing the type of course of schizophrenia in Siberian population. Disturbances in the phosphatidylinositol pathways may be a possible reason for the transition to a more severe continuous course of schizophrenia.